Ileal gastrointestinal stromal tumor presenting as retroperitoneal mass - UPRAK, TEVFİK KIVILCIM (My University, 2022)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal (GI) tract. It represents a wide range of clinical tumors with different clinical presentations, locations, and prognoses. Retroperitoneal GISTs are rarely seen and may be associated with the GI system. In this case report, we present the laparoscopic excision of retroperitoneal ileal GIST in a patient who was admitted to the outpatient clinic with abdominal pain.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Gastrointestinal stromal neoplasm; gastrointestinal stromal tumor; GISTs; ileum; retroperitoneal neoplasms; GIST; RECURRENCE; MANAGEMENT